Architectures of bulk built-in current sensors for detection of transient faults in integrated circuits. (January 2018) - Possamai Bastos, Rodrigo; Guimarães, Leonel Acunha; Sill Torres, Frank; Fesquet, Laurent
Abstract: Today's integrated circuits are liable to operate under transient faults created either by radiation or malicious sources of perturbation. Among the many techniques for the detection of transient faults, Bulk Built-In Current Sensors (BBICS) present attractive low-cost and efficient features for the protection of circuits. This article provides a survey of published BBICS architectures and compares them with regard to their sensitivities in detecting transient faults. Moreover, a new dynamic BBICS architecture is introduced with improved detection sensitivity, negligible power consumption, and reduced area overhead.